DIGITALIZING ARABIC LANGUAGE EDUCATION: EXPLORING APPROACHES, TECHNOLOGY, AND ASYNCRONOUS MEDIA IN LANGUAGE LEARNING - Nur Lathifah, Winda; Irza Maulana Al’arif; Mahda Anggita Zukini Fahma; Nada Nafila Salsabila (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
A literature review emphasizing the integration of technology in Arabic language learning in the digital age that focuses on asynchronous systems discusses advances and challenges in applying technology. Despite digital skills and internet access, innovation in learning remains promising, with applications, online platforms, and artificial intelligence underpinning rich learning experiences. Data obtained from reading articles relevant to the topic discussed. This research utilizes qualitative research methods (Systematic Literature Review) to elaborate and analyze the topic of Arabic learning in the digital era, especially in the asynchronous model. The process of analysis of collection, classification, display and conclusion. As a result, digitization in Arabic language learning involves the integration of digital technologies, using software, applications, and online platforms. This provides an advantage for students and teachers with the accessibility and flexibility of learning. Teachers who are adept at optimizing technology can create innovative, creative, and collaborative learning. The benefits of digitalization for Arabic language learning include increased access and flexibility, student interactivity, and personalization of learning according to individual needs. The literature review underscores the integration of technology in Arabic language learning in the digital age, facing challenges such as digital limitations and uneven internet access. However, there are great opportunities for innovation. The use of various applications, platforms, and artificial intelligence offers a way to enrich learning. Recommendations for the future include the development of the latest technologies, a student-centered approach, diverse digital content, and training for teachers.